Social capital in youth volunteerism / Asmidar Alias, Mohd Hafiz Mohd Nor and Mohd Faizal Musa - Alias, Asmidar; Mohd Nor, Mohd Hafiz; Musa, Mohd Faizal (2013)
The theoretical framework of social capital suggested that individuals bound together in dense social networks, infused with norms of reciprocity and trust, are better able and more inclined to act collectively for mutual benefit and social purposes as opposed to atomized individuals. The objective of social capital model is to improve and maintain the society well-being and economic efficiency. The idea is contemporary known as social capital by Robert Putnam (2000) as connections among individuals, social networks and the norms of reciprocity and trustworthiness that arise from them. This notion is therefore seen as "sociological superglue" that holds society together. The effectiveness is strongly depends on structural phenomenon and a cultural phenomenon. Recently, volunteerism has flourished within youth which give beneficial effect to local communities. It is worth to scrutinize the elements of social capital within voluntarily activities. Thus, youth volunteerism is study, highlighted based on social capital model suggested by Putnam (2000). The study is to inspect factors that bind youth in society with the case study of Teach for the Needs (Malaysia) Berhad (TFTN).